Soybean morphology and physiology in mahogany agroforestry system with organic fertilizer application. Issue 1 (1st December 2022) - Setyaningrum, D; Budiastuti, M T S; Purnomo, D; Sudadi,; Mufid, M F
Abstract: Land conversion causes a decrease in the area of agricultural land, so that agricultural cultivation efforts through agroforestry systems are needed, such as planting between mahogany trees. The aim of the study was to examine the morphological and physiological responses of soybeans to organic fertilizers in mahogany-based agroforestry systems. The study consisted of a single factor, namely the type of organic fertilizer using a completely randomized block design. Treatment of types of fertilizers with four levels, namely: chemical fertilizer, chicken, goats and cow manure. The results showed that the type of organic fertilizer affected soybean morphology, namely plant height 3 and 4 WAP, leaf number 4 WAP, and soybean physiology, namely total chlorophyll. The plant height and the number of leaves were highest in the cow manure fertilizer. Chicken manure produced the highest total chlorophyll, which was 0.0743 mg/g. Total chlorophyll count was positively correlated with the amount of chlorophyll a and b. In addition, plant fresh weight was positively correlated with plant biomass. Soybean has the potential to be cultivated in agroforestry systems and the addition of nutrients with organic fertilizers.